Report to the League of Nations on the administration of the territory of New Guinea from July 1 st, 1923, to June 30th, 1924 (League of Nations, 1925)
With index and tabs. Reports on mandatory powers. Submitted to the council of the League of Nations in accordance with Article 22 of the covenant and considered by the Permanent Mandates Commission at its Sixth Session (June-July 1925), 4. Commonwealth of Australia.